NETRALITAS APARATUR SIPIL NEGARA DALAM PEMILIHAN KEPALA DAERAH 2020 DI KABUPATEN LUWU TIMUR - Haedar Djidar; Dandi Darmadi; Fitriani Ismail (Halu Oleo University, 2024)
The neutrality of the State Civil Apparatus (ASN) is needed in political processes such as the general election of regional heads because civil servants are public services and civil servants who truly stand independently without having to take sides. The problem in this research is the neutrality of the state civil apparatus in the head election. 2020 Region in East Luwu Regency. How to impose sanctions for violations of the neutrality of the State Civil Apparatus (ASN) in the Regional Head Election (Pilkada) in East Luwu Regency in 2020. This research aims to. To find out and analyze the neutrality of the State Civil Apparatus in the 2020 Regional Head Election in East Luwu Regency. To find out how to impose sanctions for violations of the neutrality of the State Civil Apparatus (ASN) in the Regional Head Election (Pilkada) in East Luwu Regency in 2020. This research was conducted using Normative Empirical legal research methods. The research was conducted in East Luwu Regency. The East Luwu Regency Government, together with Bawaslu, in organizing the regional elections, is committed, together with Election Organizing Institutions and Non-Election Organizing Institutions, to implementing Regional Elections with integrity, namely by preventing violations and fraud in the implementation of Regional Elections. Providing sanctions for violations of the neutrality of the State Civil Service requires fact-based case handling.